Localisation of citrullinated and carbamylated proteins in the inflamed gingival tissues of rheumatoid arthritis / Lee Yin Hui - Lee, Yin Hui (2019)
Background: Antibodies to citrullinated proteins are widely used as diagnostic marker for rheumatoid arthritis (RA). Antibodies against carbamylated proteins were also suggested to be used as a potential biomarker for RA. It has been speculated that citrullination and carbamylation occur in inflamed periodontium which can be a source of autoantibodies to induce immune responses resulting in the development and progression of RA. Aim: To determine the presence and location of citrullinated and carbamylated proteins in the gingival tissues and compare their abundance in periodontitis (PD) participants with and without RA. Materials and Methods: Gingival tissue samples of healthy control (n = 5), PD with RA (n = 5) and PD without RA (n = 5) were collected. Specimens were formalin-fixed, paraffin embedded and sectioned at 4 µm. The tissue sections were analysed for the presence of citrullinated and carbamylated proteins by immunohistochemistry. Semi-quantitative analysis was performed to quantify and compare the protein abundance between groups. Results: Number of cells containing citrullinated and carbamylated proteins with higher intensity was markedly increased in gingival tissues from PD with or without RA in comparison with healthy controls. Conclusion: Inflamed gingival tissue is a potential extra-articular source of citrullinated and carbamylated proteins. The extent to which these proteins contribute to the pathogenesis of RA warrants further elucidation.